2018
DOI: 10.3389/fevo.2017.00177
|View full text |Cite
|
Sign up to set email alerts
|

Holocene Dynamics of Temperate Rainforests in West-Central Patagonia

Abstract: Analyses of long-term ecosystem dynamics offer insights into the conditions that have led to stability vs. rapid change in the past and the importance of disturbance in regulating community composition. In this study, we (1) used lithology, pollen, and charcoal data from Mallín Casanova (47 • S) to reconstruct the wetland, vegetation, and fire history of west-central Patagonia; and (2) compared the records with independent paleoenvironmental and archeological information to assess the effects of past climate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 73 publications
2
27
0
Order By: Relevance
“…1100-1400. Though less robustly according to our critical analysis, records from Mallín Casanova (Iglesias et al, 2016(Iglesias et al, , 2018 this work; ID 24, ca. 450-950 CE, evergreen forest), La Tercera (Bamonte and Mancini, 2011;this work;ID 27, ca.…”
Section: The Impact Of the Mca On Past Human Populations From Patagoniamentioning
confidence: 82%
“…1100-1400. Though less robustly according to our critical analysis, records from Mallín Casanova (Iglesias et al, 2016(Iglesias et al, , 2018 this work; ID 24, ca. 450-950 CE, evergreen forest), La Tercera (Bamonte and Mancini, 2011;this work;ID 27, ca.…”
Section: The Impact Of the Mca On Past Human Populations From Patagoniamentioning
confidence: 82%
“…Study C combines lake-sediment charcoal record with fire scars on living spruce trees (Picea) to assess response of this forest system to increasing human pressure since the gold rush (c. 1902) (Gaglioti et al, 2016). Study D presents a study of Nothofagus that revealed a long and stable persistence of this forest system over time (Iglesias et al, 2018). Study E shows a 90,000 year pollen record from an Afromontane site in Cameroon, indicating highly unstable species composition with past climate changes (Lézine et al, 2019).…”
Section: Analysis Of Contemporary Datasetsmentioning
confidence: 99%
“…Paleoecological methods for detecting stability or variability can rely on the rate of change in a pollen time-series (Iglesias et al, 2018) as well as turnover in pollen composition (e.g., Birks and Birks, 2008). First, in Patagonia, the Nothofagus (southern beeches) forest was found to have prevailed relatively unchanged for the past 9,800 years until the twentieth century by calculating the rate of change in pollen records, which was equal to zero (Iglesias et al, 2018) (Figure 3, Study D). This stability could be attributed to Nothofagus' resistance to environmental change, its ability to rapidly recover or trade-offs in the plasticity within Nothofagus' species traits.…”
Section: What Does the Paleoecological Record Suggest?mentioning
confidence: 99%
“…Mallín Casanova (47.4°S) is a broad wetland surrounded by rainforests of Nothofagus pumilio and Pilgerodendron uviferum. Radiocarbon-dated reconstructions show that the modern bog developed at 5800 cal yr BP, probably in response to the onset of wetter conditions that impacted all of Patagonia[30]. Approximately 2000 years ago, charcoal data indicate that fires became more frequent.…”
mentioning
confidence: 99%
“…(a) Wetland dynamics at Mallín Casanova (47.4°S; Chile) inferred from squared-chord distances (SCD) between every pollen sample and the first sample of the record (9500 cal yr BP). SCDs were based on a dissimilarity matrix produced for all aquatic and wetland taxa and interpreted as temporal changes in wetland composition[30]. (b) Changes in SCD between times t + 1 and t as a function of SCD at time t. The nearly horizontal, positive regression line (slope = 0.22; equation (2.1)) indicates that the wetland was in unstable equilibrium.…”
mentioning
confidence: 99%